Mechanical and sustainability performance of concrete with discarded coconut coir as an alternative to conventional sand - Balamurali Kanagaraj; Samuel V. James; R. Samuvel Raj; N. Anand (Discover Applied Sciences)
Abstract Due to increased construction activities, the demand for construction material increases, which causes depletion of natural resources such as river sand in Asian countries. Therefore, the present study aims to replace conventional sand with discarded coconut coir (CC) and examines the engineering and sustainable performance of concrete. The proportion of CC in the concrete mix was 25%, 50%, 75% and 100%. Replacement of river sand with CC tends to decline the strength from 32 to 83% after 28-d of curing. In addition to the mechanical properties, the concrete blended with CC was subjected to temperature exposure as per ISO 834 guidelines. Four different heating durations were adopted, namely, 821 ℃ (for 30 min), 925 ℃ (for 60 min), 986 ℃ (for 90 min), and 1029 ℃ (for 120 min). The mass loss in concrete with the incorporation of CC after subjecting to elevated temperature was found to be 5–14%. Strength loss was observed in the range of 61–85% after subjecting to 30–120 min of heating. In the case of environmental impacts, the carbon efficiency of the concrete without CC was 0.010 t-CO2/MPa whereas the concrete with 100% CC was found to be 0.063 t-CO2/MPa, showing that the concrete blended with CC possesses superior performance. Moreover, in the case of an economic index, the concrete blended with 100% CC possesses 81% higher efficiency than the concrete with conventional aggregates. Similarly, the sustainability index of the concrete with CC shows 83% higher efficiency.